Soil saturated hydraulic conductivity of typical revegetated plants on steep gully slopes of Chinese Loess Plateau - Zhu, Pingzong; Zhang, Guanghui; Zhang, Baojun (Geoderma, 2022)
•Saturated hydraulic conductivity (KS) decreases logarithmically with soil depth.•Revegetation greatly increases KS on steep gully slope.•Plant root plays the most important role in promoting KS.•Parameters related to soil structure are more effective to estimate KS. Soil saturated hydraulic conductivity (KS) is one of the most important hydraulic parameters for simulating water movement and solute transportation across soil profile, which is a highly variable in space. The changes in soil and vegetation properties induced by vegetation restoration (converting the steep farmland to woodland, shrub land, or grassland via artificial vegetation or natural succession) likely affect KS greatly. Nevertheless, few studies have been carried out to investigate the differences and vertical variations of KS across soil profile in arid and semi-arid regions after vegetation restoration. This study was conducted to detect the differences and vertical variations of KS across 0–200 cm soil profile under typical plants on steep gully slopes of the Loess Plateau and further to identify its dominant influencing factors. Undisturbed soil samples, collected from one bare land, two typical shrub lands, and four typical grasslands, were utilized to measure KS using the constant head method. The results showed that the mean KS varied from 0.21 to 1.47 mm min−1, and a significant difference was found between plant of Carex lanceolata (CL) and other six plants (p < 0.05). Soil saturated hydraulic conductivity of all selected testing sites (except for CL) decreased logarithmically with the increase of soil depth. The variations in KS were significantly affected by soil and vegetation properties. KS increased significantly with sand content, organic matter content (SOMC), saturated soil water content (SSWC), field capacity (FC), total porosity (TP), capillary porosity (CP), and root mass density (RMD), whereas decreased significantly with clay content and bulk density (BD). The results of partial least square regression revealed that RMD, SOMC, sand content, BD, and TP were the dominant factors attributing to the variations in KS. Furthermore, KS could be well estimated by RMD, CP and FC, and the result was more accurate compared to that estimated by the traditional pedotransfer function (PTF). These results are helpful for understanding water movement within soil profile and developing hydrological models in arid and semi-arid regions after vegetation restoration.